The Relationship between Corporate Governance and the Company’s Performance in the Stock Exchange of Thailand - Kaewkerd, Sirima; Soonthonrot, Pakaphon (วารสารการบัญชีและการจัดการ, 2020)
Research on the relationship between corporate governance and the performance of listed companies in the Stock Exchange of Thailand has the objectives as follows: 1) To study factors affecting the performance of listed companies in the Stock Exchange of Thailand and 2) To study the relationship between corporate governance and the performance of listed companies in the Stock Exchange of Thailand. Research methodology comprised empirical research and multiple regression analysis to test relationships by using the return on equity (ROE) as an indicator in the account view and Tobin’s Q as a market view. In corporate governance aspect, it will focus on the relevant structures which comprised 1) The proportion of independent external committees in the board of directors of the company; 2) The size of the board of directors; 3) The number of the board of directors meetings per year; 4) The merging of the positions of the chairperson and president as the same person and 5) The level of corporate governance score from the Report of Corporate Governance Report of Thai Listed Companies (CGR).The population was 333 companies listed on the Stock Exchange of Thailand by studying the information of the company in 2015. The study found that corporate governance had a relationship with the performance of companies on the Stock Exchange of Thailand. When considering the relationship between corporate governance and the company’s performance, it found that the proportion of non-executive directors, the size of the board of directors, the number of meetings, the merger of the chairman and the president in the same person, the level of corporate governance score had a relationship of independent variables without causing problems of Multicollinearity. Considering each aspect, it found that Size factor of the board of directors had a relationship with the performance of return on equity and the confidence rate of investors with statistical significance at the level of 0.05